Teen Dating Violence - Azim Zahir Ali; Nazish Hussain Ali (International Journal on Women Empowerment, 2015)
Adolescent dating violence is an issue that influences numerous teenagers. Indifference and clashes emerge in close relationship, which prompts dating misuse like beating, pushing, kicking, slapping and forcing partner for harmful sexual practice. These activities have a profound impact on the victim as well as to the abuser's psychological health. Approximately, 1in 5 high school female teens have experienced some form of physical and sexual violence from their dating partners. To identify intrinsic and extrinsic factors of teenage dating violence in order to eliminate its consequences. The literature review was done in the period of March-June 2015 from various online databases such as PUBMED, CINAHL, MEDLINE and Google Scholar, and other relevant research articles ranging from 2004-2015. Teen dating violence is an emerging problem of relationship in adolescence period. Teen dating violence varies in different forms. Sociocultural factors influence individuals to show abusive attitude in a relationship. Victims’ intrinsic factors inhibit them to report the violent behavior of partner. Community and school based interventions are significantly important to stop the crime occurring from our society. Teen dating violence is the leading social and public health issue causing behavioral and psychological illness in teens all over the world. For monitoring these changes in adolescence, the health care professionals have to play their key role. School based interventions are cornerstone interventions in eradicating teen dating violence from grass root level.